The Influence of Organizational Support and Job Satisfaction on Employee Performance at Truntum Hotel Padang - Ela Ardiva; Hendri Azwar (Journal of Multidimensional Management, 2025)
This study examines the influence of organizational support and job satisfaction on employee performance at Truntum Hotel Padang. Using a quantitative causal-associative approach, data were collected from 75 employees through a saturated sampling technique. Structured questionnaires were distributed, and the data were analyzed using multiple linear regression with SPSS version 25. The findings indicate that organizational support does not have a significant direct effect on employee performance, while job satisfaction exerts a positive and significant influence. Furthermore, the simultaneous test results reveal that organizational support and job satisfaction together significantly affect employee performance, with an Adjusted R² value of 0.291. This implies that 29.1% of the variation in employee performance can be explained by these two variables, while the remaining 70.9% is influenced by other factors outside the scope of this study. These results highlight the critical role of job satisfaction in enhancing employee performance in the hospitality sector and suggest that hotel management should strengthen organizational policies and practices that foster employee satisfaction and well-being to ensure sustainable service quality and competitiveness.